Rendhagyó nyomozási bíró? A bíróság elé állítás jelene és jövője - Hevér, Tibor (Debreceni Jogi Műhely, 2012)
The rules of Hungarian Criminal Procedure Code related to summary proceedings aren’t newfangled. Probably, due to the criminal policy needs, arise from that, recent years these changed considerably and in a sense went through “volte-face”. To emphasise the strong connection between this special process and the investigation, I review the rules of some surrounding states that apply to this, in order to point out in a constructive way the problems of the operative Hungarian regulations. I’d like not only to line up these for the Reader but – in search of optimal key – also make de lege feranda proposals.